Endopolyploidy is a common response to UV-B stress in natural plant populations, but its magnitude may be affected by chromosome type - Zedek, František; Plačková, Klára; Veselý, Pavel; Šmerda, Jakub; Šmarda, Petr; Horová, Lucie; Bureš, Petr (Annals of botany, 2020)
BACKGROUND AND AIMS: Ultraviolet-B radiation (UV-B) radiation damages the DNA, cells and photosynthetic apparatus of plants. Plants commonly prevent this damage by synthetizing UV-B-protective compounds. Recent laboratory experiments in Arabidopsis and cucumber have indicated that plants can also respond to UV-B stress with endopolyploidy. Here we test the generality of this response in natural plant populations, considering their monocentric or holocentric chromosomal structure. METHODS: We measured the endopolyploidy index (flow cytometry) and the concentration of UV-B-protective compounds in leaves of 12 herbaceous species (1007 individuals) from forest interiors and neighbouring clearings where they were exposed to increased UV-B radiation (103 forest + clearing populations). We then analysed the data using phylogenetic mixed models. KEY RESULTS: The concentration of UV-B protectives increased with UV-B doses estimated from hemispheric photographs of the sky above sample collection sites, but the increase was more rapid in species with monocentric chromosomes. Endopolyploidy index increased with UV-B doses and with concentrations of UV-B-absorbing compounds only in species with monocentric chromosomes, while holocentric species responded negligibly. CONCLUSIONS: Endopolyploidy seems to be a common response to increased UV-B in monocentric plants. Low sensitivity to UV-B in holocentric species might relate to their success in high-UV-stressed habitats and corroborates the hypothesized role of holocentric chromosomes in plant terrestrialization.
Keywords: Phylogeny; Arabidopsis; lidé; Chromosomes; fylogeneze; chromozomy; Plant Leaves; Ultraviolet Rays; listy rostlin; ultrafialové záření; Humans